2019
DOI: 10.3390/ijms20092121
|View full text |Cite
|
Sign up to set email alerts
|

PhSeZnCl in the Synthesis of Steroidal β-Hydroxy-Phenylselenides Having Antibacterial Activity

Abstract: We report here the reaction of in situ prepared PhSeZnCl with steroid derivatives having an epoxide as an electrophilic functionalization. The corresponding ring-opening reaction resulted to be regio- and stereoselective affording to novel phenylselenium-substituted steroids. Assessment of their antibacterial properties against multidrug-resistant bacteria, such as Pseudomonas aeruginosa Xen 5 strain, indicates an interesting bactericidal activity and their ability to prevent bacterial biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Considering our interest in the synthesis of organoselenium compounds with antioxidant activity, in light of the above-reported evidence and in the frame of our efforts to develop antimicrobial compounds [15][16][17][18], we sought to prepare novel quercetin derivatives decorated with organochalcogen moieties. These new hybrid compounds could present improved M pro inhibition and be endowed with the ability to hamper SARS-CoV-2 replication in a cellular context, thus being suitable to be considered for preclinical studies required for the development of direct antiviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…Considering our interest in the synthesis of organoselenium compounds with antioxidant activity, in light of the above-reported evidence and in the frame of our efforts to develop antimicrobial compounds [15][16][17][18], we sought to prepare novel quercetin derivatives decorated with organochalcogen moieties. These new hybrid compounds could present improved M pro inhibition and be endowed with the ability to hamper SARS-CoV-2 replication in a cellular context, thus being suitable to be considered for preclinical studies required for the development of direct antiviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…2022, 23, x FOR PEER REVIEW 3 of 11 diphenyldiselenide (PhSe)2 and other, differently functionalized diselenides [11]. This chemistry was expanded at different positions within the steroidal core by some of us who recently reported the epoxide transformation exploiting the reactivity of PhSeZnCl, obtaining selenosteroids endowed with antibiofilm activity [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that selenium compounds such as thiaselenazoles, dithiazoles, and selenium–platinum complexes are effective antimicrobial and antiviral agents [ 9 , 10 , 11 , 12 , 13 ]. These agents allow for both narrow- and broad-spectrum antimicrobial and viral activity at micromolar concentrations with limited toxicity [ 9 , 10 , 11 , 12 , 13 ]. Furthermore, these agents are effective against multidrug-resistant bacteria and the formation of bacterial biofilms [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These agents allow for both narrow- and broad-spectrum antimicrobial and viral activity at micromolar concentrations with limited toxicity [ 9 , 10 , 11 , 12 , 13 ]. Furthermore, these agents are effective against multidrug-resistant bacteria and the formation of bacterial biofilms [ 9 , 10 , 11 , 12 , 13 ]. An ideal antibacterial drug would target the virulence mechanisms of bacterial pathogens and not be affected by existing resistance mechanisms in these bacteria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%